2020
DOI: 10.1093/cid/ciaa007
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Influenza-Associated Invasive Pulmonary Aspergillosis May Not Be Universal: A Retrospective Cohort Study from Alberta, Canada

Abstract: From 2014–2019, invasive pulmonary aspergillosis complicated 7.2% (0–23.1% in different influenza seasons) of cases of influenza-associated respiratory failure in Edmonton, Alberta. Disease outcomes ranged from survival without therapy to death despite antifungals. Clinician vigilance, longitudinal local surveillance, and refined criteria to identify patients requiring therapy are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 9 publications
3
82
2
1
Order By: Relevance
“…The median time between influenza diagnosis and IAPA was short, often in the first 5 days [7,8,18]. Studies have shown considerable variation in rates of IAPA in different countries, with high rates in the Netherlands, Belgium and Taiwan, but lower rates in other countries [19], and in some we do not know the incidence (e.g., USA) [20][21][22]. Potential reasons for these regional differences are related to the underlying conditions, concomitant exposure to corticosteroids, environmental factors, including exposure to Aspergillus, use of non-culture-based diagnostic tests for Aspergillus (e.g., galactomannan (GM)) and differences in awareness of IAPA [23][24][25].…”
Section: Global Epidemiology Of Influenza and Iapamentioning
confidence: 99%
“…The median time between influenza diagnosis and IAPA was short, often in the first 5 days [7,8,18]. Studies have shown considerable variation in rates of IAPA in different countries, with high rates in the Netherlands, Belgium and Taiwan, but lower rates in other countries [19], and in some we do not know the incidence (e.g., USA) [20][21][22]. Potential reasons for these regional differences are related to the underlying conditions, concomitant exposure to corticosteroids, environmental factors, including exposure to Aspergillus, use of non-culture-based diagnostic tests for Aspergillus (e.g., galactomannan (GM)) and differences in awareness of IAPA [23][24][25].…”
Section: Global Epidemiology Of Influenza and Iapamentioning
confidence: 99%
“…Invasive aspergillosis (IA) complicating severe influenza pneumonia is well-described from anecdotal case reports, and more recently from cross-centre and large cohort studies (1)(2)(3)(4)(5). Of particular note, mortality was significantly higher in patients with influenza/aspergillosis than those with influenza alone (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…As influenza seemed independently associated with IPA, the term influenza-associated pulmonary aspergillosis (IAPA) was introduced [1,2]. In contrast, a single-center retrospective Canadian study reported an incidence of 7.2% [3]. Incidence seemingly varies between geographical regions and centers, but awareness among physicians may also vary.…”
mentioning
confidence: 99%